2008
DOI: 10.1091/mbc.e08-03-0272
|View full text |Cite
|
Sign up to set email alerts
|

Role of the RAM Network in Cell Polarity and Hyphal Morphogenesis inCandida albicans

Abstract: RAM (regulation of Ace2p transcription factor and polarized morphogenesis) is a conserved signaling network that regulates polarized morphogenesis in yeast, worms, flies, and humans. To investigate the role of the RAM network in cell polarity and hyphal morphogenesis of Candida albicans, each of the C. albicans RAM genes (CaCBK1, CaMOB2, CaKIC1, CaPAG1, CaHYM1, and CaSOG2) was deleted. All C. albicans RAM mutants exhibited hypersensitivity to cell-wall- or membrane-perturbing agents, exhibiting cell-separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
103
1
22

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(132 citation statements)
references
References 70 publications
(89 reference statements)
6
103
1
22
Order By: Relevance
“…As in budding yeast, the RAM network is required for Ace2 function in C. albicans (44,59), and regulatory sites by which S. cerevisiae Cbk1 controls Ace2 are preserved in the C. albicans Ace2 ortholog (data not shown). While it is not clear if RAM network function is downstream of Cdc14 in C. albicans, the high degree of conservation of the system's components suggest that a similar regulatory organization might exist in this diverged yeast.…”
mentioning
confidence: 93%
“…As in budding yeast, the RAM network is required for Ace2 function in C. albicans (44,59), and regulatory sites by which S. cerevisiae Cbk1 controls Ace2 are preserved in the C. albicans Ace2 ortholog (data not shown). While it is not clear if RAM network function is downstream of Cdc14 in C. albicans, the high degree of conservation of the system's components suggest that a similar regulatory organization might exist in this diverged yeast.…”
mentioning
confidence: 93%
“…For instance, in MOR mutant cells from S. pombe, C. albicans and N. crassa, the actin cytoskeleton appears dispersed around the cell cortex (Hou et al, 2003;Song et al, 2008;Verde et al, 1998;Ziv et al, 2009). In contrast, in C. neoformans it was described that the hyperpolarized growth associated to RAM mutants correlated with abnormal actin localization at the growing tips (Walton et al, 2006).…”
mentioning
confidence: 99%
“…Kamthan et al (2014) observed that depletion of MPS1 through the use of a methionine-regulated allele led to actively dividing cells with buds lacking nuclei, indicating that MPS1 is required for proper mitosis. Song et al (2008) had also previously shown that mitotic defects were present in cbk1D/D strains. We therefore examined the nuclear segregation of the corresponding single and double heterozygous cbk1 and mps1 strains.…”
Section: Mitotic Defects Of Mps1 Mutants Are Exacerbated By Loss Of Cmentioning
confidence: 71%
“…In S. cerevisiae, Cbk1 plays functions in the mitotic exit network (MEN) and in the regulation of cytokinesis (Weiss 2012). In addition, C. albicans cells lacking components of the RAM pathway show increased levels of multinucleate cells (Song et al 2008). MPS1 expression is increased by hyphae-inducing conditions in a PKA/Efg1-dependent manner (Kamthan et al 2014).…”
Section: Mitotic Defects Of Mps1 Mutants Are Exacerbated By Loss Of Cmentioning
confidence: 99%
See 1 more Smart Citation